Role performance of special education teachers : problems and prospects - Reddy, G. Lokanadha; Jayaprabha, R.; Sujathamalini, J. (New Delhi, India : Discovery Pub. House, 2005)
Study conducted in Andhra Pradesh and Tamil Nadu states of India.
Includes index.
EDU
Keywords: Special education educators -- Rating of -- India -- Andhra Pradesh; Special education educators -- Rating of -- India -- Tamil Nadu